DETERMINATION OF FACTORS AFFECTING THE CHOICE CAR MAINTENANCE AND REPAIR SERVICES - Karahan, Mehmet; Dinç, Hasan (Kyrgyz-Turkish Manas University, 2016)
Nowadays, in which there is intense and rapid competition, one of the most important factors that plays an active role for companies to maintain its survival and growing is to be ensure satisfaction of costumer who is provided with end product in global competitive environment . Today, the company's most valuable asset is customer that is the main reason for companies creation. Companies seek different methods to get new costumers or continuity of customers that it already has. In this context, the identification of the factors that affect customer satisfaction, provides a huge competitive advantage for companies. Thus it is needed to investigate this issue. If companies fulfill their customers’ needs and expectations at the highest level, it will increase its profit as well as its permanence The purpose of this study is to determine in what extent car owners are satisfied with the repair and maintenance services they receive and to determine the factors affecting customers about choosing special or authorized services. Research sample is composed of about 200 customers who use of car services in Diyarbakir. Research is conducted face to face interviews and the data obtained is transferred to SPSS 18 program and is went through some statistical analysis, the results are exhaustively commented and relevant recommendations have been developed.

Rekabetin yoğun ve hızlı olarak yaşandığı günümüzde, küresel rekabet ortamında işletmelerin varlıklarını devam ettirebilmeleri ve büyüyebilmelerinde etkin rol oynayan faktörlerin başında son ürünün sunulduğu müşterinin memnun edilmesidir. Günümüzde müşteri, işletmenin en değerli varlık sebebi olmuştur. İşletmeler yeni müşteri kazanabilmek veya sahip olduğu müşterilerin devamlılığını sağlamak için değişik yöntemler aramaktadırlar. Bu bağlamda müşteri memnuniyetine etki eden faktörlerin belirlenmesi, işletmeler açısından büyük bir rekabet avantajı sağladığından bu araştırmaya gerek duyulmuştur. İşletmelerin müşteri istek ve beklentilerini en yüksek düzeyde karşılaması, hem tutundurmasını hem de karlılık oranını arttıracaktır Bu çalışmanın amacı, otomobil sahiplerinin bakım ve onarım için hizmet aldıkları servislerden ne derece memnun olduklarını, müşterilerin özel veya yetkili servis tercihlerini etkileyen faktörleri belirlemektir. Araştırma örneklemini Diyarbakır ilinde otomobil servis hizmetlerinden yararlanan yaklaşık 200 müşteri oluşturmaktadır. Araştırma yüz yüze anket yöntemi ile yapılmış ve elde edilen veriler SPSS 18 programına aktarılarak önce frekans ve yüzde hesapları, sonra t-testi ve f testi yapılarak elde edilen sonuçlar ayrıntılı olarak yorumlanmış ve konuyla ilgili öneriler geliştirilmiştir
Otomobil Bakım ve Servis Hizmetleri Tercihine Etki Eden Faktörlerin Belirlenmesi